Suppression of AGO2 by miR-132 as a determinant of miRNA-mediated silencing in human primary endothelial cells. (December 2015) - Leonov, German; Shah, Kunal; Yee, Daniel; Timmis, Jon; Sharp, Tyson V.; Lagos, Dimitris
Abstract: The abundance of miR-132 ranges from constitutively high in the brain where it is necessary for neuronal development and function, to inducible expression in haematopoietic and endothelial cells where it controls angiogenesis and immune activation. We show that expression of AGO2, a protein central to miRNA-mediated gene silencing and miRNA biogenesis, is negatively regulated by miR-132. Using HeLa cells, we demonstrate that miR-132 interacts with the AGO2 mRNA 3′UTR and suppresses AGO2 expression and AGO2-dependent small RNA-mediated silencing. Similarly, miR-132 over-expression leads to AGO2 suppression in primary human dermal lymphatic endothelial cells (HDLECs). During phorbol myristate acetate (PMA)-activation of HDLECs, miR-132 is induced in a CREB-dependent manner and inhibition of miR-132 results in increased AGO2 expression. In agreement with the role of AGO2 in maintenance of miRNA expression, AGO2 suppression by miR-132 affects the steady state levels of miR-221 and miR-146a, two miRNAs involved in angiogenesis and inflammation, respectively. Our data demonstrate that the miRNA-silencing machinery is subject to autoregulation during primary cell activation through direct suppression of AGO2 by miR-132.